Cyber-secure pneumatic actuator system equipped with encrypted controller and attack detectors. (3rd May 2022) - Shin, Takaya; Teranishi, Kaoru; Kogiso, Kiminao
Abstract : A cyber-secure and flexible actuator is essential for cyber-physical-human systems. The use of wireless communication in such systems improves their usability but adds cybersecurity risks. This study proposes a cyber-secure flexible antagonistic pneumatic artificial muscle (PAM) actuator system. The proposed PAM actuator system has an encrypted proportional-integral controller and a real-time detector for cyberattacks. The controller is concealed in the encrypted control fashion using a homomorphic encryption scheme with security parameter 64 bit, and the control signal is computed over a cipher space. The detector has a threshold to detect significant changes in control inputs caused by cyberattacks such as signal injection and parameter falsification. The experimental results demonstrate that the proposed PAM actuator system achieves the desired control performance and improves the reliability of control operations under cyberattacks. The main contribution of this study is the first implementation of an encrypted controller for a pneumatic actuator to develop a secure PAM actuator with real-time detection of cyberattacks. The results of this study contribute to the future development of safe remote systems that interact with humans in the medical and industrial fields. GRAPHICAL ABSTRACT: UF0001